2001
DOI: 10.1159/000047353
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiographic Evaluation of Left-Ventricular Diastolic Function in Patients with Chronic Pulmonary Hypertension

Abstract: Different patterns of left-ventricular (LV) diastolic dysfunction were reported in patients with pulmonary hypertension (PHT). There are no data regarding the relationship between the severity of PHT and LV diastolic dysfunction. In order to determine the severity of PHT at which LV diastolic dysfunction occurs and to identify its pattern, we studied by Doppler echocardiography 120 patients with PHT (57 with severe PHT and 63 with mild or moderate PHT) and compared them with 75 normal controls. Systolic pulmon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
29
0
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 24 publications
(35 reference statements)
1
29
0
2
Order By: Relevance
“…Several authors have previously noted the high prevalence of LV diastolic dysfunction in patients with PAH. [1][2][3]14 However, most of these studies included patients with chronic thromboembolic disease or a heterogenous group of patients with PAH. In our cohort, which consisted of carefully selected patients with hemodynamic criteria for PAH, 9 we observed that nine out of 10 patients had impaired LV relaxation (grade I diastolic dysfunction) by echocardiographic criteria, with redistribution of the LV fi lling from early to late diastole.…”
Section: Relationship Of LV Diastolic Function With Hemodynamics Paramentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have previously noted the high prevalence of LV diastolic dysfunction in patients with PAH. [1][2][3]14 However, most of these studies included patients with chronic thromboembolic disease or a heterogenous group of patients with PAH. In our cohort, which consisted of carefully selected patients with hemodynamic criteria for PAH, 9 we observed that nine out of 10 patients had impaired LV relaxation (grade I diastolic dysfunction) by echocardiographic criteria, with redistribution of the LV fi lling from early to late diastole.…”
Section: Relationship Of LV Diastolic Function With Hemodynamics Paramentioning
confidence: 99%
“…[1][2][3] Little is known, however, about its association with severity of disease and outcomes in patients with idiopathic or heritable PAH, since most of the studies were done on subjects with chronic thromboembolic disease or included a heterogeneous group of patients with PAH.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(119,120) Tutar et al (121) described the left ventricular diastolic function impairment in COPD patients, and a similar correlation between right ventricular pressure and E/A ratio, and IVRT. Schena et al (5) also demonstrated that the right ventricular pressure correlates with left ventricular eccentricity indexes; the distorted ventricular geometry results in its abnormal filling pattern in turn.…”
Section: Vidiscussionmentioning
confidence: 83%
“…Some investigators, however, suggest the presence of subclinical systolic dysfunction in the COPD patients. (110) Suchon´ et al (105) found that ejection fraction, shortening fraction and lateral mitral annular peak systolic velocity in COPD patients, were in the normal value range and did not differ significantly from control group. Similar results were obtained by other investigators.…”
Section: Vidiscussionmentioning
confidence: 97%